Faktor-faktor yang mempengaruhi rasio pembayaran dividen pada perusahaan FMCG (Fast Moving Consumer Goods 2016-2020) - Kurniawan, Aditya; Gandakusuma, Imo (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The distribution of company profits to shareholders on invested capital through dividends, previous profits, or buying back shares. One of the provisions reviewed in this meeting is the provision regarding the determination or not of dividends or what is better known as dividend policy (policy). The purpose of this study was to determine the effect of ownership structure and cash flow on the dividend payout ratio of the FMCG industry listed on the Indonesia Stock Exchange (IDX). This research was conducted using panel regression analysis with a random effects approach. This study uses secondary data obtained from the quarterly reports of Fast Moving Consumer Good companies listed on the Indonesia Stock Exchange (IDX) for 5 years from 2016 – 2020 using a purposive sample. The results of the panel data regression test show that the institutional ownership variable has a significant effect on the dividend payout ratio. Variable operating cash flow (OCF) and free cash flow (FCF) each partially has a significant effect on the dividend payout ratio. This research is expected to provide an additional reference in deciding how the dividend level to be given (dividend payout ratio) and to identify aspects that can affect the dividend payout ratio, investors who want a dividend return can be more careful in selecting the company where they want to invest their money. demanded. The company (practitioner / financial manager) continues to prioritize good governance in carrying out its business activities. This is so that there is no conflict (agency problem) between management and shareholders because this conflict will be detrimental in the future. . Investors should also explore what rights they have as shareholders and the regulations that protect these rights